Legal Prerequisites for Gender Discrimination in the Russian Federation - D. T. Karamanukyan (Сибирское юридическое обозрение)
In this article, for the first time in the domestic legal science, an attempt has been made to conduct a comprehensive inter-sectoral analysis of the institution of gender equality in the current Russian legislation. The Author, based on normative and empirical sources, as well as the results of various sociological studies, critically analyzes the leading branches of the national law of the Russian Federation in the comparative context of the scope of rights and freedoms of men and women. Guided by international public law and case-law of judicial courts of the Russian Federation, the Author proposes to make changes to a number of provisions enshrined in the current Russian legislation in order to restore the gender balance necessary in a social-legal state.